Effectiveness Of Home Visit On Drug Compliance In Adult Hipertens In Gadung Puskesmas Buol District - Lilis Suryani (Chakra Brahmanda Lentera Institute, 2019)
Background: Hypertension has become a deadly disease in many developed countries and has developed over the last eight decades. Hypertension that occurs for a long time and continuously can trigger a stroke, heart attack, heart failure, and is a major cause of chronic kidney failure. For those who have these risk factors should be more vigilant and earlier in making prenventive efforts, for example, compliance control or routine blood pressure control, supervision and scheduling routine medication more than once during a Home Visit, and try to avoid triggering factors Hypertension. Objective To find out whether there is an influence of Home Visit on Compliance in Taking Medication in Elderly Hypertension in Gadung Public Health Center in Buol District.The design used in this study is Pre-experimentation (One Group pre-posttets design). The population is all elderly with hypertension. The sample size was 38 respondents using simple random sampling technique. The independent variable of the study is the home visit. The dependent variable is medication adherence. Data were collected using a questionnaire, then data were analyzed using Wilcoxon test with a significance level of α ≤ 0.05.The results showed that the majority of respondents before the intervention had non-compliance compliance as many as 25 respondents (65.8%), after the intervention had obedience as many as 28 respondents (73.7%), the statistical test in the study used Wilcoxon test with a <0.05 obtained p = 0,000 where H1 was accepted and H0 was rejected, which means that there was an influence of Home Visit on Medication Compliance in Hypertensive Elderly in Gadung Public Health Center, Buol RegencyThere is an influence of Home Visit Against Compliance with Medication in Elderly Hypertension in Gadung Public Health Center, Buol Regency.